Alkoxyphenyl or alkylphenyl side-chained Thieno[2, 3-f]benzofuran polymer for efficient non-fullerene solar cells. (June 2020) - Wang, Dongxue; Cui, Wen; Li, Feng; Yang, Mingqun; Jing, Xin; Yu, Liangmin; Sun, Mingliang
Abstract: In this work, two novel thieno[2, 3-f]benzofuran (TBF) unit, with fluorinated alkoxyphenyl or alkylphenyl side chain, were synthesized and characterized. Based on these TBF donor unit and benzodithiophene-4, 8-dione (BDD) acceptor, two novel polymers, PTBFPF-BDD and PTBFP-BDD, were prepared by Stille coupling reaction. The conjugated side chain effects on the thermogravimetric, optical, electrochemical, and photovoltaic properties of these polymers were systematically investigated. Both polymers exhibited desirable power conversion efficiency (PCE) of more than 8% after thermal annealing. PTBFP-BDD:ITIC-based devices achieved higher PCE of 8.50% with an open-circuit voltage ( V OC ) of 0.88 V, a short-circuit current density ( J SC ) of 16.01 mA/cm 2 and a fill factor (FF) of 59.80%. In addition, the devices based on PTBFPF-BDD:ITIC showed an enhanced V OC of 0.92 V due to down-shifted the highest occupied molecular orbital (HOMO) energy levels. The results indicate that the alkylphenyl/alkoxyphenyl substitution of TBF donor units is promising strategy for improving PCE of PSCs. Graphical abstract: Image 1 Highlights: Novel thieno [2, 3-f]benzofuran monomer, with fluorinated alkoxyphenyl or alkylphenyl side chain, were firstly reported. Both thieno [2, 3-f]benzofuran based polymer show desirable power conversion efficiency (PCE) of more than 8%. The photovoltaic results are good among thieno [2, 3-f]benzofuran backboned polymer.